If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 65 + -4x = 5x + 18 Reorder the terms: 65 + -4x = 18 + 5x Solving 65 + -4x = 18 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 65 + -4x + -5x = 18 + 5x + -5x Combine like terms: -4x + -5x = -9x 65 + -9x = 18 + 5x + -5x Combine like terms: 5x + -5x = 0 65 + -9x = 18 + 0 65 + -9x = 18 Add '-65' to each side of the equation. 65 + -65 + -9x = 18 + -65 Combine like terms: 65 + -65 = 0 0 + -9x = 18 + -65 -9x = 18 + -65 Combine like terms: 18 + -65 = -47 -9x = -47 Divide each side by '-9'. x = 5.222222222 Simplifying x = 5.222222222
| (6w+5)-w= | | log(x)*25=2 | | 5a-1=11 | | 16=12x-1 | | 3*1.6=x | | 11a+15b+4c+3c-6b-5a= | | 0.05x+.06(20000-x)=1740 | | 20p+17q+p-7q-5p= | | 14m+6n-5m+8n= | | X^2-4=1 | | 8x-3=9x+7 | | 2x^2-3x-20= | | 2r+8=-1 | | -4a+24+7a=3a-8a | | 5x+2x-3=24 | | 7/8x-3+1/4x=5/24x+1/6 | | 12a+11b+2c+6c-2b-4a= | | 14x^3+35x-7= | | x/7+3=-4 | | 15x^2+55x= | | c-21c+21=0 | | -3=-6w-7 | | -90=7x+3x | | 3x^7+21x^4-54x^3= | | x-9x+8=0 | | x/2=-10+2 | | 3.5x-5+3=-15 | | a(13)=5-2(15) | | -8n+16=-4n-16 | | y=30+25x | | -2a^0(x^-6y^3z^2)^-1/(6x^-4)(y^-1)(z^3) | | 55+5x=8x+16 |